2003
DOI: 10.1074/jbc.m300370200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human Proguanylin

Abstract: The endogenous ligand of guanylyl cyclase C, guanylin, is produced as the 94-amino-acid prohormone proguanylin, with the hormone guanylin located at the COOH terminus of the prohormone. The solution structure of proguanylin adopts a new protein fold and consists of a three-helix bundle, a small three-stranded ␤-sheet of two NH 2 -terminal strands and one COOHterminal strand, and an unstructured linker region. The sequence corresponding to guanylin is fixed in its bioactive topology and is involved in interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Additionally, it was shown for prouroguanylin that the hormone part exclusively adopts the A-form topology after digestion of the prohormone and release of the mature hormone region [10], which is the same as observed in the proguanylin structure (Fig. 3 B) [27]. Based on these findings it has been suggested that prouroguanylin adopts a fold similar to that of proguanylin [27], allowing comparative modelling of the prouroguanylin structure (Fig.…”
Section: Oligomerization State Of Proguanylin and Prouroguanylinsupporting
confidence: 56%
See 3 more Smart Citations
“…Additionally, it was shown for prouroguanylin that the hormone part exclusively adopts the A-form topology after digestion of the prohormone and release of the mature hormone region [10], which is the same as observed in the proguanylin structure (Fig. 3 B) [27]. Based on these findings it has been suggested that prouroguanylin adopts a fold similar to that of proguanylin [27], allowing comparative modelling of the prouroguanylin structure (Fig.…”
Section: Oligomerization State Of Proguanylin and Prouroguanylinsupporting
confidence: 56%
“…3 B) [27]. Based on these findings it has been suggested that prouroguanylin adopts a fold similar to that of proguanylin [27], allowing comparative modelling of the prouroguanylin structure (Fig. 3 C).…”
Section: Oligomerization State Of Proguanylin and Prouroguanylinmentioning
confidence: 75%
See 2 more Smart Citations
“…The proforms of guanylin and uroguanylin were chosen as coatings for guanylin and uroguanylin competitive ELISAs to ensure binding and competition of A-form-specific antibodies (48). The cDNA sequences of proguanylin (IMAGE ID 100062076) and prouroguanylin (IMAGE ID 7939624; http://www.imageconsortium.org) were cloned into the pSXG vector (49) as GST fusions.…”
Section: Methodsmentioning
confidence: 99%